Cancer Patients with Chronic Pain and Their Caregivers during COVID-19: A Descriptive Study - Cristina Costeira; Filipe Paiva-Santos; Nelson Pais; Ana Filipa Sousa; Ivo Paiva; Dulce Helena Carvalho; Ana Rocha; Filipa Ventura (MDPI AG, 2023)
Background: The sanitary measures imposed by COVID-19 intensified challenges in the pain management of cancer patients. Methods: A descriptive study was conducted in a chronic pain unit of an oncological hospital aiming to explore the experiences of cancer patients with chronic pain and their caregivers during the pandemic period, as well as identify strategies to improve care in chronic pain management. An electronic questionnaire was developed containing sociodemographic variables, the Depression, Anxiety and Stress Scale-21, and open-ended questions exploring the experiences and circumstances of pain management. Results: A total of 30 patients and 13 caregivers filled in the questionnaire. Patients revealed a higher level of depression, anxiety, and stress than caregivers, without statistically significant differences. Both groups mentioned having experienced difficulties in self-care, particularly in relation to sleep, nutrition, and recreation. In total, 83.7% patients needed pain relief medication related to uncontrolled pain. Both mentioned that they would have benefited from a digital application to ease the communication with the healthcare professionals of the chronic pain unit, as well as non-pharmacological interventions, such as therapeutic massage. Conclusions: Recognizing that chronic pain leads to significant limitations, it is essential to implement and anticipate objective and effective responses in pain management.